The Effect of Inflation and Earnings Per Share On Profitability In BUMN Companies From 2019-2021 - Pamungkas, Amos Haposan; Hutabarat, Francis; Ulyreke, James Slyvanus (Universitas Indo Global Mandiri Palembang, 2023)
Abstract Investors, in general, evaluate a company's ability to generate profits based on current events, where the company's profit performance, earnings per share value and also inflation movements play an important role. BUMN is a state-owned company that has a large reach to society. The index that monitors the price performance of the best BUMN shares is the BUMN20 Index. Evaluations are carried out periodically on shares listed in the BUMN20 Index. The population in this study are companies listed on the BUMN20 Index listed on the Indonesia Stock Exchange (BEI) in 2019-2021 with a total of 20 companies. The sampling technique used, namely the purposive sampling method, is based on obtaining a sample that is able to represent the population, 60 research samples have been obtained. The variables of this research are inflation, earnings per share and profitability and will be measured using PSPP statistical software. The research results noted that there was an insignificant influence between inflation and profitability in BUMN20 index companies. Meanwhile, earnings per share were found to have a significant influence on state-owned companies from 2019-2021. The results of the F test simultaneously note that inflation and EPS have an effect on profitability.